2000
DOI: 10.1021/ma990983o
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Mid-IR Monitoring of the Initiation and Propagation in Epoxi-Initiated Living Isobutylene Polymerizations

Abstract: The initiation and propagation of isobutylene (IB) polymerization initiated by 1,2-epoxi-2,4,4-trimethylpentane (TMPO-1)/TiCl 4 was monitored by a new fiber-optic transmission mid-IR probe. The real-time IR data provided insight into the initiation mechanism. Polyether formation, isomerization of the TMPO-1 into 2,4,4-trimethylpentanal, and its complexation by TiCl4 were observed, which occurred simultaneously with initiation of IB polymerization. The proposed initiating mechanism involves the formation of ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
(30 reference statements)
2
22
0
Order By: Relevance
“…For instance, MSE showed 40% I eff , while TMPO-1 had less than 1% I eff . In-situ FTIR monitoring gave further insight into the initiation step, [61] supporting the proposed initiating mechanism. Controlled initiation with external epoxides such as MSE would yield a primary hydroxyl head group and a tertchloride end group.…”
Section: B) New Initiators For Carbocationic Polymerizationmentioning
confidence: 62%
“…For instance, MSE showed 40% I eff , while TMPO-1 had less than 1% I eff . In-situ FTIR monitoring gave further insight into the initiation step, [61] supporting the proposed initiating mechanism. Controlled initiation with external epoxides such as MSE would yield a primary hydroxyl head group and a tertchloride end group.…”
Section: B) New Initiators For Carbocationic Polymerizationmentioning
confidence: 62%
“…For example, maximum initiation efficiencies of 40% where reported for R-methylstyrene epoxide, and apparently lower efficiencies were obtained for molecular weight targets under 4000 g/mol. 16 The low initiation efficiencies were caused by epoxide rearrangement (e.g., formation of aldehydes) and formation of polyethers, 17 the extent of such side reactions being determined by the initiator structure. 18 Knoll et al 19 demonstrated the in situ synthesis of allyl chloride-terminated PIB by charging 1,3-butadiene to BCl 3 -catalyzed isobutylene polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic investigation on cationic polymerization of IB has been conducted by in situ FTIR 33–36. The strength of peak at 887 cm −1 reflects directly the concentration of IB in polymerization system 33–36.…”
Section: Resultsmentioning
confidence: 99%